Pembinaan modul stem belantara berteraskan nilai murni bagi pendidikan Orang Asli - Serman, Nur Sahrizan (2021)
Indigenous students are those who are dropout of education especially in the field of STEM. Aboriginal people consider STEM education to be insignificant and have no impact on their lives. They also have a low self-concept such as shy and sensitive which makes it difficult for them to change their lives that are very close with the nature. Therefore, this study was conducted to help indigenous students in the field of STEM with input of noble values by inserting the elements of nature through the development of the ‘Modul STEM Belantara’. This module integrates 7 characteristics of STEM teaching and learning outlined by the Ministry of Education Malaysia and 16 noble values adapted from the National Education Philosophy in 5E learning model. This module was developed through ADDIE Teaching Design which involves five phases namely analysis, design, development, implementation and evaluation. This study has used quantitative study design to test the validity and reliability of the module. A total of 13 assessors were selected which are from STEM field instructors who have at least 5 years of teaching experience using module evaluation instruments. Module validity was conducted with a module content validity value eith 94% while the reliability through inter-rater reliability (IRA) with 0.95 that indicates high module validity and reliability. This is supported by the positive comments given by the evaluators on the module. Therefore, ‘Modul STEM Belantara’ that has been developed can be used to attract indigenous students in the field of STEM with noble values.